Peradilan In Absentia Pada Perkara Tindak Pidana Korupsi - P. Iskandar Welang (Faculty of Law, Universitas Lampung, 2020)
The Corruption Criminal Court in absentia is a deviation or prohibited because it is considered as a violation of the defendant's human rights so that the right of the defendant to make a defense will be lost or ignored as regulated in Article 196 Paragraph (1) of the Criminal Procedure Code. Judgment in absentia is only permitted for perpetrators of traffic violations. Then what if the court in absentia is applied to corruption cases. The method in this research uses an approach that includes an empirical approach carried out through direct research in the field, and a normative approach carried out through literature studies related to legislation, research results and other literature. In the implementation of the court in absentia for corruption cases do not violate the rights of the suspect because the defendant is still given the right to follow the stages for criminal justice both from the process of investigation, investigation and trial, but in this case the defendant does not want to use or utilize the rights their rights which have been granted and guaranteed by laws and regulations as regulated in the Criminal Procedure Code.